Seroepidemiological survey on sporotrichosis-infection in rural areas of the south of Minas Gerais State, Brazil - Grisolia, Julianne Caravita (Braz J Microbiol, 2020)
Sporotrichosis is a subcutaneous mycosis caused by traumatic inoculation into the skin by fungi species of the genus Sporothrix. The disease has different clinical manifestations (cutaneous, lymphocutaneous, and disseminated), and can also progress to a systemic infection. Despite having a worldwide distribution, sporotrichosis is most prevalent in tropical and subtropical countries. In Brazil, reports of the disease are higher frequent, where cases of the disease were found in Rio de Janeiro, Sao Paulo, Curitiba, Pernambuco, and Paraiba, among others. Certain groups of people may be more exposed to the causative agent of disease, such as residents of rural areas. Thus, this work aimed to carry out a seroepidemiological survey of the prevalence of sporotrichosis in four rural locations in the south of Minas Gerais State, Brazil. In this study, we used an indirect ELISA test in the survey on the prevalence of sporotrichosis. Data obtained in this study evaluated a population of 631 individuals and showed a prevalence of 44.69%. The distribution of seroprevalence of sporotrichosis with respect to age groups and gender showed no significant statistical difference. Thus, we found a high seroprevalence of sporotrichosis-infection in rural regions of southern Minas Gerais State, Brazil, with no difference in prevalence in relation to gender and age.